Language policy: CIS and Kazakhstan experience - Abasilov, А.; Kenes, A. (KU Publ., 2022)
The article provides a comparative analysis of the language policy experience in the CIS countries and the Republic of Kazakhstan. To understand the current language situation in Kazakhstan, the achievements and shortcomings of the language policy of the countries coming from the Soviet system are demonstrated. To improve the state language policy, models that exist in the CIS countries and proposals useful for Kazakh science are presented. The current state of the state language, the peculiarities of the development of the language situation in multiethnic countries, including the methods adopted by the CIS countries to solve the problems of forming the state language policy determine the need for a new language policy in Kazakh society. This indicates the relevance of the study. The study describes the impact of the difficult language situation in Kazakhstan after gaining independence on the state language policy. Based on the current language situation, the direction of further progress of language policy in the Republic of Kazakhstan will be determined. Considering the experience of language policy in the Baltic states when the language situation was similar to Kazakhstan, significant phenomena in the course of their implementation allow Kazakhstan to develop and implement a more effective language policy concerning national and foreign languages. Within the framework of the specifics of language policy in these countries, issues of functioning, and Status features, a review of legislation will be conducted. As an example, the reforms in the field of language that prompted Alash figures to do this, as well as the works of scientists who were engaged in systematic improvement of the use of the native language in life, both in the later and modern periods, are given. Data on the language policy of Kazakhstan in the Soviet system and documents on the state language policy in modern Kazakhstan are analyzed. Looking at historical and social factors affecting the policy, activity, and development of the state language from the point of view of social linguistics, the authors make proposals for the development of the status and policy of the state language.
Tіл саясаты: ТМД елдері мен Қазақстандық тәжірибе
Языковая политика: опыт стран СНГ и Казахстана
Keywords: language policy; language situation; language planning; language development practice; state language; Kazakh language